Revisiting the concept of social integration and its implications for national unity: the experience of Muslims in the Philippines - Gamon, Alizaman Dumangcag (2019)
This paper highlights the experience of Muslims in the Philippines towards the integration of their ancestral territorial roots, language and customs and traditions. It is often viewed that education provides a distinctive pattern of transmitting cultural values and norms to its young and potential members. However, because of the prevalence of secularism in the Philippines, economics, law, cultural and educational reform have been constantly revised and changed following the popular trends coming from the West. It is indeed unfortunate that the framework of the government policies for social integration and development were crafted in accordance with the interests of the ruling elites in the country. In addition, the government approach for national integration via education reform has lost its identity, which has resulted in the widening of socio-economic and cultural gap between Christian majority and Muslim minority societies. The study aims at re-examining the strengths and flaws of government agendas for social integration, particularly in dealing with the legal, economic and educational reform in the Autonomous Region in Muslim Mindanao (ARMM). Although the philosophy of Islamic knowledge, Islamic worldview and epistemology are not well spell out in the government policies and laws for the integration of Muslims in the national body politics, the study seeks to explore how the gradual restoration of tawhidic epistemology and integration of knowledge could serve the interest of intercultural discourse and national unity. In addition, the study seeks to discuss the possible areas for the integration project by which, the popularization of Shari’ah and its maqasid dimension will put Muslim communities in new positive light in the eyes of humanity. As such, the unresolved root of conflict emanating from the intellectual segregation will be addressed. The result of the study would serve as a framework for policy makers since it examines the challenges on how to generate experts on integration of knowledge as a new strategy for transforming higher institutions of learning in the Muslim areas as a leading universities and private colleges in the country. What obstructed the growth and development of Muslim society are the general lack of freedom and the decades of interference in academic and scholarly institutions on the part of the government and security forces. Leaving aside the many issues in understanding the politics of integration as experienced by Muslims in the Philippines, the following recommendations can be tentatively made in the present study: first and foremost, which is the most delicate in a Muslim minority setting, is the need for the systematic development of a holistic understanding of the various branches of knowledge, from which, tawhidic worldview and epistemology are duly recognized as relevant for the realization of integration through education, such move should not be seen as dichotomous modes of existence but as seamless continuum in the history of education in the Philippines. Secondly, to achieve the desired objective of the integration can be spearheaded by Muslim government agencies and organizations in order to build bridges and channels of academic, scientific and technical cooperation with other systems and educational institutions at the regional and global level. Thirdly, the human nature and philosophy of integration of knowledge should serve the interest of the entire mankind